The impact of childcare on maternal employment - Bence Szabó; Judit Berei; Márton Csillag; Hanna Erős; Judit Krekó; Ágota Scharle (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2022)
This paper examines the effect of childcare availability on maternal employment in Hungary based on 2016 Microcensus data. We exploit the exogenous variation in access to childcare due to informal admission practices based on the date of birth, to identify the effect of childcare availability on maternal employment and the children's enrolment. We find that on average, expanding the coverage of nurseries to the same level as kindergartens would lead to around 7.3 percentage points higher maternal employment, an around 25% higher employment rate compared to the baseline of mothers with a child aged 2-2.5 years. At the same time, the decomposition of the link between childcare availability and employment shows that enrolment would increase by 17.7 percentage points due to the higher coverage, close to 40% compared to the baseline. Enrolment in childcare would increase maternal employment probability by around 41 percentage points, around two-thirds of the employment rate of mothers. We also examine the heterogeneities of the effect along demographic characteristics using causal forests, and the economic cycle by expanding the analysis to the 2011 Census. We find that in 2016 the childcare availability effect is higher for mothers with 3 children, living in villages, or municipalities without nurseries. The employment effect is lower in the 2011 Census, while the effect on enrolment in formal childcare remains similar, suggesting the importance of weaker labour demand in 2011.
Keywords: J13; J22; 330; mothers' labour supply; childcare availability